2018
DOI: 10.1055/s-0038-1668132
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Effects of Dabigatran in Paediatric Patients Compared with Adults: Combined Data from Three Paediatric Clinical Trials

Abstract: Background  Physiological age-related changes in the haemostatic and coagulation systems result in differing anticoagulant assay responses to standard anticoagulants. Therefore, we investigated the response of anticoagulant assays to dabigatran etexilate (DE) in children compared with adults. Objective  This article assesses the relationship between plasma dabigatran concentration and coagulation assay results across age groups in children and adults. Patients and Methods  Data from three clinical trials in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…142 Only dabigatran has published pharmacokinetic data in children showing similarities to adults with the exception of longer clotting times in children younger than 1 year. 143 Pediatric pharmacokinetic data for the remaining DOACs are limited to in vitro experiments 144 and case reports that suggest possible differences compared to adults. 145 Similar to adult studies, children with CrCl <30 to 50 ml/min are excluded from the aforementioned studies, making it unlikely that safety and efficacy data will be generated for childhood CKD in the near term.…”
Section: Childhood Kidney Diseasementioning
confidence: 99%
“…142 Only dabigatran has published pharmacokinetic data in children showing similarities to adults with the exception of longer clotting times in children younger than 1 year. 143 Pediatric pharmacokinetic data for the remaining DOACs are limited to in vitro experiments 144 and case reports that suggest possible differences compared to adults. 145 Similar to adult studies, children with CrCl <30 to 50 ml/min are excluded from the aforementioned studies, making it unlikely that safety and efficacy data will be generated for childhood CKD in the near term.…”
Section: Childhood Kidney Diseasementioning
confidence: 99%
“…It is generally accepted and recommended by regulatory agencies that pediatric dosing should lead to exposure comparable to that of adult levels, if a similar PK/PD relationship has been demonstrated . Data from an in vitro study, previous phase II pediatric VTE studies of dabigatran, and a subsequent pooled analysis of pediatric PK/PD data, demonstrate that the PK/PD relationship observed in pediatric patients (from birth to <18 years old) was fairly consistent across ages, with the exception of those aged <1 month, and was similar to that seen in adults with VTE . Therefore, for the current study it was deemed appropriate to target dabigatran exposure levels shown to be effective in the adult population.…”
Section: Methodsmentioning
confidence: 82%
“…Although differences exist in the pathophysiology of pediatric and adult VTE the principal pathological causes outlined in the Virchow triad (vessel wall abnormality, blood flow disturbances, and coagulability of the blood) largely apply to both. PD data obtained from previous studies indicate that the response to dabigatran in children is similar to that seen in adults . Based on these similarities and in line with FDA guidelines, it was considered reasonable to assume that DE will be effective in pediatric patients.…”
Section: Methodsmentioning
confidence: 85%
“…[5], anticoagulation has the capacity to avoid thrombus propagation, allowing sinus recanalization. Chronic use of oral anticoagulants may be difficult in children and has limitations, including the need for coagulation monitoring and drug and food interactions; however, new drugs such as thrombin inhibitor have been tested in children and demonstrate safety and efficacy [10]. The main indication for an endovascular approach is clinical deterioration despite anticoagulation [5].…”
Section: Discussionmentioning
confidence: 99%